2002
DOI: 10.1063/1.1457533
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of CoCrPt films by anomalous x-ray scattering and extended x-ray absorption fine structure

Abstract: The correlation of elemental chemistry with the particular long-range order in question cannot be obtained by common conventional characterization techniques. Here we report a study of determining the elemental concentrations of the textured Bragg diffraction peak and the averaged local atomic environment of sputtered CoCrPt films using anomalous x-ray scattering and extended x-ray absorption fine structures. The elemental compositions of the textured peak in these polycrystalline nanostructured films differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Since Cr did not preferentially segregate to grain boundaries, a resultant higher magnetic exchange coupling [20] and reduced magnetocrystalline anisotropy constant [21] would reduce the coercivity. Since Pt is known to increase the local disorder and thus coercivity by increasing the magnetocrystalline anisotropy [22], the lower coercivity of 60 nm film [5] suggested that less Pt existed in the CoCrPt (002) Bragg peak, compared with that of 30 nm film. This argument is consistent with the observed higher Cr content (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Cr did not preferentially segregate to grain boundaries, a resultant higher magnetic exchange coupling [20] and reduced magnetocrystalline anisotropy constant [21] would reduce the coercivity. Since Pt is known to increase the local disorder and thus coercivity by increasing the magnetocrystalline anisotropy [22], the lower coercivity of 60 nm film [5] suggested that less Pt existed in the CoCrPt (002) Bragg peak, compared with that of 30 nm film. This argument is consistent with the observed higher Cr content (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CoCrPt films [5] The magnetic properties of sputtered magnetic Co-Cr based films, as longitudinal and perpendicular recording media materials, are controlled by the alloy composition and the degree of phase separation of Co and Cr, the alignment of the columnar structures, the degree of Cr segregation at the grain boundaries and the mosaic of the texture. It is important to achieve a proper crystallographic texture with optimal composition to control the magnetocrystalline anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the momentum transfer along the specular direction is measured. It is a different measurement technique as compared to anomalous XRD (diffraction at a fixed momentum transfer), 16 diffraction anomalous fine structure (DAFS, absorption at a fixed momentum transfer), 17 and crystal truncation rod (CTR, surface sensitive). 18 Figure 3(b) shows the XANES result collected simultaneously with the XRD measurement.…”
mentioning
confidence: 99%